Awareness of sexually transmitted infections and cervical cancer among women in urban slums of Mumbai, Maharashtra, India - Naik, D. D.; Donta, Balaiah; Nair, Saritha; Mali, B. N. (International Journal Of Community Medicine And Public Health, 2017)
Background: Cervical cancer is one of the most common cancers among women. Due to this disease 80 percent die at an advance stage. This may be due to lack of awareness and knowledge, lack of access to proper treatment including screening facility. This study is undertaken with an objective to investigate knowledge attitude, practice and health seeking behaviour about sexually transmitted infections (STIs) and cervical cancer among eligible women in a slum community in Mumbai. Methods: Baseline data of women was drawn from an intervention study entitled “Enhancing knowledge and promoting health seeking behaviour of couples on sexually transmitted infections and cervical cancer in urban slums of Mumbai” for this article. This data was collected from a random sample of 1958 women in reproductive age group through a semi-structured interview schedule from two urban slums of Mumbai. Information was collected on socio-economic and demographic characters, awareness and symptoms of STIs and cervical cancer, and health seeking behaviour. Results: The study revealed that majority of women had heard about the STIs, 37.7 percent were aware of cervical cancer whereas only 3.6 percent of women were aware of Pap smear test. About 11 percent of women experienced at least one symptom of STI, 0.3 percent of women reported of having sexual partner other than spouse. Most women were not aware of STIs symptoms specific to men. Conclusions: Study concludes that the need to disseminate knowledge regarding STI symptoms, cervical cancer and Pap smear test for early detection of cervical cancer as well as promoting better health seeking behaviour with respect to cervical cancer and STIs. Considering of sensitivity of the topic it is necessary to design separate programmes for women.